2015
DOI: 10.1007/s40011-015-0514-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phenanthrene and Pyrene on Cytogenetic Stability of Human Dermal Fibroblasts Using Alkaline Comet Assay Technique

Abstract: In the present study, the influence of phenanthrene and pyrene on cytogenetic stability of human dermal fibroblasts using alkaline comet assay was evaluated. The cells were isolated from foreskin samples obtained from healthy male infants and in low passages (P 1-3) were exposed to various concentrations (0.0900, 0.0625, 0.0320, and 0.0066 ppm) of phenanthrene and pyrene. Then, alkaline comet assay was performed to investigate the influence of these compounds on DNA damage and cytogenetic stability of human de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[ 23 ], the expression of this gene in BM samples from AML (acute myeloid leukemia) patients did not show a statistically significant difference compared to normal samples. Conversely, other studies have shown Ang1 upregulation in AML patients, either in BM or PB samples [ 24 - 29 ]. In a study by Cheng et al .…”
Section: Discussionmentioning
confidence: 86%
“…[ 23 ], the expression of this gene in BM samples from AML (acute myeloid leukemia) patients did not show a statistically significant difference compared to normal samples. Conversely, other studies have shown Ang1 upregulation in AML patients, either in BM or PB samples [ 24 - 29 ]. In a study by Cheng et al .…”
Section: Discussionmentioning
confidence: 86%
“…The expression of P53 gene is associated with the cell cycle of myeloblasts and the cellular internal and external messages in acute myeloid leukemia (AML) [14]. As well as cytogenetic instability and mutation in proto-oncogenes due to chemical toxic materials [15,16] which can affect P53 expression [17]. It has been thought that the percentage of lymphoblasts is linked with the status of the cell cycle in ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…PAHs are ubiquitous environmental contaminants and enter the environment through various ways that are found in soil, air, water, and food sources (16,17). PAH compounds are known as human carcinogens that spread during incomplete combustion of organic matter by industrial and other human activities (e.g., combustion of urban sewage, garbage, natural gas, vehicle traffic, aluminium smelters, tobacco smoking, cooking, power plants chemical, asphalt works, petrochemical, and oil industries) as well as natural processes like burning coal and wood or forest fires (18)(19)(20)(21). Natural crude oil and kerosene contain significant amounts of PAHs (22).…”
Section: Introductionmentioning
confidence: 99%